Protein-lipid interactions and non-lamellar lipidic structures in membrane pore formation and membrane fusion - Gilbert, R (Elsevier, 2015)
Pore-forming proteins and peptides act on their targeted lipid bilayer membranes to increase permeability. This approach to the modulation of biological function is relevant to a great number of living processes, including; infection, parasitism, immunity, apoptosis, development and neurodegeneration. While some pore-forming proteins/peptides assemble into rings of subunits to generate discrete, well-defined pore-forming structures, an increasing number is recognised to form pores via mechanisms which co-opt membrane lipids themselves. Among these, membrane attack complex-perforin/cholesterol-dependent cytolysin (MACPF/CDC) family proteins, Bax/colicin family proteins and actinoporins are especially prominent and among the mechanisms believed to apply are the formation of non-lamellar (semi-toroidal or toroidal) lipidic structures. In this review I focus on the ways in which lipids contribute to pore formation and contrast this with the ways in which lipids are co-opted also in membrane fusion and fission events. A variety of mechanisms for pore formation that involve lipids exists, but they consistently result in stable hybrid proteolipidic structures. These structures are stabilised by mechanisms in which pore-forming proteins modify the innate capacity of lipid membranes to respond to their environment, changing shape and/or phase and binding individual lipid molecules directly. In contrast, and despite the diversity in fusion protein types, mechanisms for membrane fusion are rather similar to each other, mapping out a pathway from pairs of separated compartments to fully confluent fused membranes. Fusion proteins generate metastable structures along the way which, like long-lived proteolipidic pore-forming complexes, rely on the basic physical properties of lipid bilayers. Membrane fission involves similar intermediates, in the reverse order. I conclude by considering the possibility that at least some pore-forming and fusion proteins are evolutionarily related homologues. This article is part of a Special Issue entitled: Pore-Forming Toxins edited by Mauro Dalla Serra and Franco Gambale.